THE CONCEPT OF EDUCATION IN MALAY SOCIETY FROM A PHILOSOPHICAL PERSPECTIVE - Tarwiyani, Tri; Ratnasari, Sri Langgeng; Sari, Monika; Yanti, Fitri; Hutagaol, Novita Mandasari; Argadinata, M. Pratama; Ruslan, Ruslan (Universitas Labuhanbatu, 2025)
Purpose—Curriculum changes in Indonesia, which often feel far from the values and cultural roots of Indonesian society and tend to be Western, can impact the erosion of the noble values of the Indonesian nation. This research aims to explore the values that exist in the literary works of the Malay community, which in this case are found in Pantun, Tunjuk Ajar, and Gurindam.Methodology—This research is a literature study. Library research involves collecting library data, reading, taking notes, and processing data from the reading results.Findings – 1. Malay people who identify themselves with Islam indirectly use Islamic values as the reference and highest value system. Education in Malay society aims to create a perfect human who upholds all the norms held by Malay society. Perfect people in Malay society are called “bertuah”.2. Creating a person “bertuah” is the duty of all members of society, especially parents. Meanwhile, the tools and means include literary works, songs, and advice. Malay society focuses more on cultivating religious values, such as religious knowledge. Therefore, education, in this case, is more aimed at creating a character- characteristics possessed by people “bertuah.